A systematic review of workplace ergonomic interventions with economic analyses. - Tompa E; Dolinschi R; de Oliveira C; Amick BC III; Irvin E (Journal of Occupational Rehabilitation, 2010)
Introduction This article reports on a systematic review of workplace ergonomic interventions with economic evaluations. The review sought to answer the question: 'what is the credible evidence that incremental investment in ergonomic interventions is worth undertaking?' Past efforts to synthesize evidence from this literature have focused on effectiveness, whereas this study synthesizes evidence on the cost-effectiveness/financial merits of such interventions. Methods Through a structured journal database search, 35 intervention studies were identified in nine industrial sectors. A qualitative synthesis approach, known as best evidence synthesis, was used rather than a quantitative approach because of the diversity of study designs and statistical analyses found across studies. Evidence on the financial merits of interventions was synthesized by industrial sector. Results In the manufacturing and warehousing sector strong evidence was found in support of the financial merits of ergonomic interventions from a firm perspective. In the administrative support and health care sectors moderate evidence was found, in the transportation sector limited evidence, and in remaining sectors insufficient evidence. Conclusions Most intervention studies focus on effectiveness. Few consider their financial merits. Amongst the few that do, several had exemplary economic analyses, although more than half of the studies had low quality economic analyses. This may be due to the low priority given to economic analysis in this literature. Often only a small part of the overall evaluation of many studies focused on evaluating their cost-effectiveness.